Prognostic factor for prolonged ventilator usage and ICU occupancy time after mitral valve replacement surgery: a retrospective cohort study - . Supomo; Herpringga Lara Sakti; Galih Asa Andrianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
This study was conducted to identify the prognostic factors for prolongedventilator usage time and ICU occupancy time after mitral valve replacement(MVR) surgery. It was a retrospective cohort study involving 70 MVR surgerypatients at Dr. Sardjito General Hospital, Yogyakarta, Indonesia during theperiod of January 2013 to December 2018. Prognostic factors as independentvariables including age, gender, heart failure, ejection fraction, pulmonaryhypertension, chronic pulmonary disease, active endocarditis, renalinsufficiency, duration of aortic cross clamp (AOX) time and cardiopulmonarybypass (CPB) time were evaluated. Where as the dependent variables werethe prolongation of ventilator usage time (>24 h) and the intensive care unit(ICU) occupancy time (>96 h). Of the total 70 studied patients, 25 patients(35.7%) used ventilator >24 h, meanwhile 15 patients (21.4%) occupied the ICU>96 h. Patients who used ventilator >24 h had CPB time ≥126.5 min (OR=10;95%CI=2.581-41.252), renal insufficiency (OR= 14; 95%CI = 1.487-150.970), andactive endocarditis (OR=7; 95%CI = 1.257-45.213). Meanwhile, patients whooccupied the ICU >96 h had age ≥40 years old (OR=6.4; 95% CI = 1.26-15.3),CPB time ≥126.5 min (OR=5.7; 95% CI = 1.8-38.1), and heart failure with NYHAfunctional classification 3 (OR=9.8; (95% CI = 1.4-67.2). In conclusion, theprognostic factors for prolonged ventilator usage time after MVR surgery areCPB time ≥126.5 min, renal insufficiency and active endocarditis. Furthermore,the prognostic factors for prolonged ICU occupancy time are age ≥40 years old,heart failure with NYHA functional classification 3 and CPB time ≥126.5 min.